2011
DOI: 10.1007/s00330-011-2357-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of breast MR imaging in pre-operative determination of invasive disease for ductal carcinoma in situ diagnosed by needle biopsy

Abstract: MR mammography permits more precise lesion assessment including ductal carcinoma in situ A correct diagnosis of occult invasion before treatment is important for clinicians This study showed the potential of MR mammography to diagnose occult invasion Treatment and/or aggressive biopsy can be given with greater confidence MR mammography can lead to more appropriate management of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
33
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 29 publications
9
33
1
Order By: Relevance
“…When microinvasion or frank invasion ensues, the imaging findings tend to become more typically suspicious 19 . Therefore, masses are more common among invasive neoplasms, especially when portraying spiculated margin, strong initial enhancement followed by washout (Type 3 curve), or other suspicious descriptors, as we have shown in concordance to others 20 . The interest in DWI as a diagnostic and predictive surrogate biomarker for breast malignancy has increased in parallel to improvements in MRI technique [21][22][23] .…”
Section: Discussionsupporting
confidence: 70%
“…When microinvasion or frank invasion ensues, the imaging findings tend to become more typically suspicious 19 . Therefore, masses are more common among invasive neoplasms, especially when portraying spiculated margin, strong initial enhancement followed by washout (Type 3 curve), or other suspicious descriptors, as we have shown in concordance to others 20 . The interest in DWI as a diagnostic and predictive surrogate biomarker for breast malignancy has increased in parallel to improvements in MRI technique [21][22][23] .…”
Section: Discussionsupporting
confidence: 70%
“…Our MR imaging examination frequently revealed high signal intensity within DCIS lesions after letrozole treatment. Strong high signal intensity on fat-suppressed T2-weighted imaging is rare in DCIS (Goto et al , 2012), and it may reflect oedematous stroma (Yuen et al , 2007) and/or accumulation of foam cells in DCIS tissues by letrozole treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If an imaging marker predictive of DCIS upstaging to invasive carcinoma at surgery can be identified using routine imaging, clinicians may be able to better manage patients with underestimated invasive breast cancer. Previous work using radiologist‐identified features has shown that MRI has the potential to diagnose occult invasive disease in DCIS patients . The purpose of this study is to expand upon this previous work by assessing the ability of semiautomatically assessed MRI features to predict DCIS upstaging to invasive carcinoma at the time of surgery.…”
mentioning
confidence: 97%
“…While a CNB is typically sufficient for a pathologist to make a diagnosis of DCIS, the small total volume of tumor sampled by CNB may miss adjacent invasive cancer. At the time of definitive surgery, upstaging to invasive disease occurs in 3.5–56% of cases . A meta‐analysis of DCIS upstaging rates by Brennan et al concluded an average upstaging rate of 25.9%, while Lee et al reviewed the literature to find an average rate of 20.9%.…”
mentioning
confidence: 99%